Clinical Characteristics and Risk Factors of Ischemic Stroke in A Sample of Young Adults in Beni-Suef Governorate, Egypt - Mahmoud, Mustafa Ahmed; Elkareem, Shaimaa Ali Abd; Masoud, Mohammed Mabrouk (Journal of Neonatal Surgery, 2025)
Background: Ischemic stroke is the most prevalent etiology of mortality and prolonged disability, accounting for more than 80% of all types of strokes. Aim: To assess clinical features and risk factors of ischemic stroke in a sample of young adults in Beni-Suef Governorate, Egypt. Patients and methods: This case-control research was performed on 188 subjects divided into 2 groups: 93 Egyptian cases diagnosed with acute ischemic stroke were evaluated when they were admitted to the Neurology Department, Beni-Suef University Hospital (they were enrolled from February 2021 to April 2022) and the control group: included 95 healthy volunteers free of any medical illness from the same geographical region (Beni-Suef governorate). The ischemic stroke cases and the controls were matched concerning age, gender, and socioeconomic status. Results: This study revealed that 55.9% of cases had a moderate degree of stroke, with 36.6% having a mild degree versus 7.5% with moderate to severe, according to NIHSS score. The mean NIHSS score was 7.65±4.5, and the mean infarction size was 26.3±37.1 ml. Stroke etiologies were determined according to TOAST classification; the most common etiology was atherosclerotic large vessel disease (30.1%), followed by cardioembolic stroke (24.7%). Conclusion: Our study found insignificant variance in age and sex between the stroke cases and controls. Common risk factors included smoking, dyslipidemia, family history of stroke, diabetes, hypertension, and cardiac illness. Most strokes were moderate in severity, with atherosclerotic large vessel disease and cardioembolic stroke being the most common causes.